2020
DOI: 10.1017/s1478951520000711
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial assessing a pragmatic intervention to improve supportive care for family caregivers of patients with lung cancer

Abstract: Objective Family caregivers (FCs) of cancer patients often experience high distress. This randomized clinical trial assessed the feasibility and preliminary effects of an intervention to improve FC supportive care. Method A pragmatic and minimal intervention to improve FC supportive care was developed and pretested with FCs, oncology team, and family physicians to assess its relevance and acceptability. Then, FCs of lung cancer patients were randomized to the intervention or the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(45 citation statements)
references
References 51 publications
(79 reference statements)
0
44
1
Order By: Relevance
“…Early palliative care interventions reduced caregivers' anxiety levels (Aubin et al, 2021;Dionne-Odom et al, 2021). Caregivers in the EPC arm had lower anxiety at Week 24 (Dionne-Odom et al, 2021) and decreased over time (Aubin et al, 2021).…”
Section: Distressmentioning
confidence: 96%
See 1 more Smart Citation
“…Early palliative care interventions reduced caregivers' anxiety levels (Aubin et al, 2021;Dionne-Odom et al, 2021). Caregivers in the EPC arm had lower anxiety at Week 24 (Dionne-Odom et al, 2021) and decreased over time (Aubin et al, 2021).…”
Section: Distressmentioning
confidence: 96%
“…McDonald et al, 2017). Five studies showed no significant differences between intervention and comparison groups' QoL of cancer patients' caregivers (Aubin et al, 2021;Brims et al, 2019;Dionne-Odom et al, 2015;El-Jawahri et al, 2017;McDonald et al, 2017). One study did not report the difference between groups (Clark et al, 2013).…”
Section: Study Characteristicsmentioning
confidence: 97%
“…Studies have explored the effect of psychosocial interventions on caregivers of patients with advanced lung cancer 22 23 and those with non-surgical lung cancer. 24 DuBenske et al 22 found that caregivers of patients with advanced non-small cell lung cancer in the intervention group who received the comprehensive health enhancement support system experienced a lower caregiver burden and less negative mood than those in the control group who received standard care after 6 months of the intervention. Badr et al 23 also found that caregivers of patients with advanced lung cancer who received psychosocial telephone intervention showed significantly decreased anxiety, depression and caregiver burden compared with the usual care control group at an 8‐week follow‐up.…”
Section: Introductionmentioning
confidence: 99%
“…Badr et al 23 also found that caregivers of patients with advanced lung cancer who received psychosocial telephone intervention showed significantly decreased anxiety, depression and caregiver burden compared with the usual care control group at an 8‐week follow‐up. Aubin et al 24 revealed that providing pragmatic intervention for family caregivers of patients newly diagnosed with non-surgical lung cancer was not effective in reducing their anxiety and depression. On the contrary, the qualitative assessment of the intervention by family caregivers was positive as they unanimously appreciated it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation